The Link Between Venous and Arterial Thrombosis: Is There a Role for Endothelial Dysfunction? - Marco Paolo Donadini; Francesca Calcaterra; Erica Romualdi; Roberta Ciceri; Assunta Cancellara; Corrado Lodigiani; Monica Bacci; Silvia Della Bella; Walter Ageno; Domenico Mavilio (Cells)
Venous thromboembolism (VTE) and arterial thrombosis (AT) are distinct yet closely related pathological processes. While traditionally considered separate entities, accumulating evidence suggests that they share common risk factors, such as inflammation and endothelial dysfunction (ED). This review explores the parallels and differences between venous and arterial thrombosis, with particular attention to the role of unprovoked VTE and its potential links to atherosclerosis and systemic inflammation. A key focus is the role of ED, which is emerging as a critical factor in thrombogenesis across both the venous and arterial systems. We examine the current methods for clinically detecting ED, including the use of biomarkers and advanced imaging techniques. Additionally, we discuss novel research avenues, such as the potential of endothelial colony-forming cells and other innovative methodologies, to further unravel the complex mechanisms of thrombosis. Finally, we propose future clinical scenarios where targeting endothelial health could pave the way for more effective prevention and treatment strategies in thrombosis management.